The Effect of Psychological Capital and job Motivation in Improving the Productivity of Employees (A case study: Tabas coal company) - Mozhgan Hamidi Beynabaj; Khadejeh aerab shybani (مدیریت بهره وری, 2017)
Objective: The aim of the present study was to investigate the psychological capital and job motivation in promoting the employee productivity of Tabas Coal Company. Due to the nature and objectives of the study, it was an applied research and the correlation method was used for carrying it out.The statistical population of this research consisted of Tabas coal company‘s employees in 2015.Although on the basis of logic calculation of sample size in limited communities the sample size was 350 numbers, after visiting the site and collecting the questionnaires only 200 of them were completely and accurately answered and they were qualified for scoring. For collecting the data the Luthanz’s psychological capital questionnaire (2007), Amabayl and et al. job preference questionnaire (1994), and human resources productivity questionnaire based on the Chyv model by Hersey and Goldsmith (1980) whose validity and reliability were confirmed.To analyze the data in inferential statistics level, correlation coefficient, stepwise regression, and path analysis were used. The result showed that there was a significant positive relationship between all aspects of psychological capital with job productivity.Conclusion: Also the result showed that motivation in the relationship between psychological capital and job productivity plays a mediating role.